In search of the master’s degree: autoiographical performances (Palíndromo, 2020)
The present text describes and analyzes the performance “In search of the master’s degree”,2005 - 2007, series produced between the academy and the street, and how this processwas transformed by the author/artist into an autobiographical duracional performance. Theact of writing about performance art requires a multidisciplinary approach involving severalareas of knowledge on borders of the art and the life, so the use of poetic language and me-talanguage were resources explored throughout the textual composition.
Keywords: performance art in Bahia; autobiography; body; contemporary art